KOMPETENSI GURU MIN SABANG DALAM MELAKSANAKAN EVALUASI PEMBELAJARAN; Telaah atas Konstruksi Instrumen Penilaian Berbasis Kurikulum 2013 - Realita Realita (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2019)
This study aims to obtain information about the competence of MIN Sabang teachers in compiling authentic assessment instruments, and to find forms of difficulties faced by teachers in developing cognitive, affective, and psychomotor instruments. This is a qualitative research with descriptive approach method with document study questionnaire, and interview data collectio technique. Documentation data were analyzed in accordance with the rules for preparing questions, and questionnaire was analyzed quantitatively using percentage formula. The interview data were analyzed thematically. Based on the distribution of questionnaire data to 27 MIN Sabang teachers, document study and interview with 6 teachers of the school, the findings shwoed that MIN Sabang teachers had good competence in developing cognitive assessment instruments, but were less competent in developing affective and psychomotor assessment instruments. The perceived difficulties in preparing assessment instruments are in developing indicators of basic competence, determining operational verbs, compiling communicative languages, arranging aspects that are assessed, adjusting between indicators and question instruments/aspects of assessment, and determining options for answers to the question of multiple choices and matching items.